2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1094>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of malignant mesothelioma cell lines: cDNA array study

Abstract: To reveal genes relevant for malignant mesothelioma (MM), we carried out cDNA array experiments on 4 MM cell lines and 2 primary mesothelial cell cultures established from pleural fluid of non-cancer patients. Human cancer gene filters including 588 genes were used for the cDNA array experiments. Our study revealed 26 over-expressed genes that play a role in the regulation of cell fate, cell cycle, cell growth and DNA damage repair and 13 under-expressed genes encoding growth factors, receptors and proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Cellular Transformation by Human JAGGED1-Although aberrant misexpression of DSL proteins has been documented in several tumor types, a causal role in oncogenesis has not been demonstrated (29,(47)(48)(49). Here, we report that expression of JAGGED1 transforms RKE cells in culture.…”
Section: Discussionmentioning
confidence: 82%
“…Cellular Transformation by Human JAGGED1-Although aberrant misexpression of DSL proteins has been documented in several tumor types, a causal role in oncogenesis has not been demonstrated (29,(47)(48)(49). Here, we report that expression of JAGGED1 transforms RKE cells in culture.…”
Section: Discussionmentioning
confidence: 82%
“…In MM, different molecular alterations lead to cyclin D overexpression or cyclin D-CDK hyperactivity (Kettunen et al, 2001;Lee et al, 2007) and a correlation between high cyclin D1 expression and decreased p27 level has also been shown . Consistent with the role of SRC in inducing cyclin D1 gene (CCND1) expression at the transcriptional level (Sinibaldi et al, 2000), we observed a significant CCND1 mRNA downregulation in MSTO-211H and REN cells treated with SI83 and SI91 for 72 h (Figure 3e), which was confirmed also at the protein level (Figure 3f).…”
Section: Src Inhibition Increases P27 Nuclear Localizationmentioning
confidence: 96%
“…We have successfully used the microarray technique for detecting altered expression patterns in several forms of cancer, including malignant mesothelioma, sarcomas and leukaemia (Wolf et al, 2000;Aalto et al, 2001;Kettunen et al, 2001). In this study we describe the use of cDNA array technology for the detection of specific expression patterns for pulmonary adenocarcinomas, and describe genes that are differentially expressed in primary lung tumours as compared to normal lung tissue.…”
Section: Introductionmentioning
confidence: 99%